Stopping healthcare misinformation: The effect of financial incentives and legislation. Issue 5 (May 2021) - Au, Cheuk Hang; Ho, Kevin K.W.; Chiu, Dickson K.W.
Highlights: Financial incentives impact on sharing healthcare information positively regardless of validity. Financial incentives impact stronger on attracting readers to share fake healthcare misinformation. Legislation deter sharing true healthcare information but not those perceived fake. Abstract: Fake news and misinformation have become a major social issue. And yet, many researchers concern primarily about political misinformation, leaving healthcare misinformation less emphasized. Nevertheless, healthcare misinformation may create consequences such as delayed diagnosis or treatment of patients or even public health crisis. We conducted an online experiment to test the role of financial incentives and legislation on disseminating online healthcare misinformation. Our findings revealed that financial incentives have a positive but diminishing impact on the likelihood of sharing online healthcare information regardless of validity. However, financial incentives have a stronger impact on attracting readers to share healthcare misinformation that they perceived to be fake. Surprisingly, legislation may deter the sharing of healthcare information that users perceive to be true but cannot deter them from sharing the healthcare misinformation they perceive to be fake. We also provided some practical implications for formulating measures of battling against healthcare misinformation for policymakers.